Antithesis as a principle of organising a literary text (based on H. Bazin’s trilogy «La famille Rezeaux») - Tuchynskі Alіakseі V. (Journal of the Belarusian State University. Philology, 2025)
On the material of H. Bazin’s trilogy «La famille Rezeaux» the role of antithetical relations in the organisation of the literary text is investigated. The oppositions of grammatical, lexical and compositional units are analysed. The composition of the text is considered from the point of view of content and form. Attention is paid to the influence of the principle of antithesis on the components of the content plan, in particular on themes, images, events, etc. Oppositions of such components of the plan of expression, as elements of text architectonics, characters’ lines and author’s words, are studied.